Spatial Analysis of The Effect of HDI and NET Wages of Informal Workers on Poverty in Central Java - Ahmad Za’iimul Chanief; Chotib Chotib; Amin Mudzakkir (Eduvest - Journal of Universal Studies, 2024)
This study analyzes the spatial influence of the Human Development Index (HDI) and net wages of informal workers on poverty rates in Central Java. Informal workers in Central Java have high poverty potential, so this study investigates the correlation between informal workers' net income and poverty rates in Central Java. Spatial analysis was also conducted to understand the spatial effects on the regression of HDI and informal workers' income on poverty. The theoretical framework includes the concepts of poverty, HDI, and informal workers. The data used in this study is data from 2022 with the dependent variable being the percentage of poverty, and the independent variables being HDI and the average monthly income of informal workers in each district/city in Central Java. The analysis method uses classical regression and spatial regression, each using Microsoft Excel and GeoDa applications. The results of the analysis show that HDI and the average net income of informal workers have a significant effect on the poverty rate in Central Java. Spatial analysis showed the existence of spatial clustering of poverty, and spatial regression confirmed the absence of spatial autoregression or spatial error in the model.